INFLUENCE OF CREDIT FACILITIES ON FINANCIAL PERFORMANCE OF WOMEN OWNED ENTERPRISES IN NAKURU, KENYA - Jepkomen, Bridgid; Kiplagat, Nehemiah; Kibet, Lawrence (. The Strategic Journal of Business & Change Management, 2024)
Women-owned micro and small enterprises face significant challenges in achieving optimal financial performance. Despite their vital role in the economy, these businesses encounter various obstacles that hinder their growth and sustainability. Therefore, the study sought to assess the influence of credit facilities on financial performance of women owned enterprises in Nakuru, Kenya. The study was anchored on Tradeoff theory. The study used a descriptive research design. The population of the study comprised 682 Micro and small enterprises that are owned by women entrepreneurs in Rongai Sub-County, Njoro Sub-County and Bahati Sub- County. This study used a systematic random sampling to select those women who participate in Rotating Savings and Credit Associations. The sample size of 252 business women was obtained using Yamane, formula. Data was collected using structured questionnaires. A pilot study was conducted in Kericho County. Both face and content validity were assessed. An internal consistency technique was adopted to measure reliability of research instruments. All the variables had Cronbach overall value of 0.863 which was greater than 0.7. Quantitative analysis was used to analyze descriptive statistics. The study found a positive and significant relationship between credit facilities and the financial performance of women-owned enterprises in Nakuru, Kenya. From the findings the study concluded that credit facilities have statistically significant influence on financial performance of women enterprises in Nakuru, Kenya. From the findings the study recommends that ROSCA should encourage a culture of regular savings by promoting consistent contributions among members. They should also provide opportunities for members to build their creditworthiness within the ROSCA and explore partnerships with formal financial institutions to facilitate access to additional credit options
Keywords: Financial Performance, Credit Facilities and Women Owned Enterprises